2013
DOI: 10.1080/00918369.2013.835618
|View full text |Cite
|
Sign up to set email alerts
|

Do LGBT Aging Trainings Effectuate Positive Change in Mainstream Elder Service Providers?

Abstract: This study aims to provide empirical evidence regarding whether attitudes, beliefs, and intentions of elder-service providers can be positively affected as a result of attending cultural competency training on the unique challenges of sexual and gender minorities. Stigmatization throughout the lifespan may have a causal influence on barriers to care, social isolation, and concomitant health disparities. Data were collected for this study at 4 Massachusetts training events to pilot a cultural competency worksho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 23 publications
(34 reference statements)
1
62
0
3
Order By: Relevance
“…Debido a esto, su implicación nos parece esencial para que la diversidad sexual dentro de las residencias sea contemplada y se respeten los derechos de los residentes LGBT, eliminado cualquier vestigio de actitudes prejuiciosas o práctica discriminaría tanto en los profesionales como en entre los residentes (Hillman, 2017). Así, son ellos los primeros responsables de asegurar unos cuidados de alta calidad y respetuosos con los derechos de los residentes (Donaldson & Vacha-Haase, 2016;Porter & Krinsky, 2014).…”
Section: Conclusionesunclassified
“…Debido a esto, su implicación nos parece esencial para que la diversidad sexual dentro de las residencias sea contemplada y se respeten los derechos de los residentes LGBT, eliminado cualquier vestigio de actitudes prejuiciosas o práctica discriminaría tanto en los profesionales como en entre los residentes (Hillman, 2017). Así, son ellos los primeros responsables de asegurar unos cuidados de alta calidad y respetuosos con los derechos de los residentes (Donaldson & Vacha-Haase, 2016;Porter & Krinsky, 2014).…”
Section: Conclusionesunclassified
“…Il ressort de recherches américaines que les programmes de formation sur les expériences de vie et les besoins des aînés gais et lesbiennes offerts dans les organisations publiques de santé ont des impacts positifs sur le développement des compétences culturelles des praticiens, en favorisant une meilleure compréhension des disparités en matière de santé, une connaissance des ressources LGBT et l'adoption de comportements préconisant des environnements respectueux et inclusifs pour les aînés non hétérosexuels (Hardacker, Rubinstein, Hotton et Houlberg, 2014 ;Porter et Krinsky, 2014). Jacobs et Kane (2012) proposent plusieurs recommandations pour améliorer la formation des intervenants auprès des hommes gais et bisexuels aînés.…”
Section: Implications Et Recommandationsunclassified
“…40 One study found that providing LGBT aging sensitivity training to service providers resulted in positive change at least in the short term. 41 A first step in developing sensitivity and understanding is exploring one's own homophobic or heterosexist biases. 19,25 Hospice and palliative care organizations can learn from the policies and practices of LGBT organizations such as Services and Advocacy for GLBT Elders (SAGE).…”
mentioning
confidence: 99%